Relationship between Exchange Rates and Stock Prices – GCC Perspectives - Aladwani, Jassim (International Journal of Economics and Financial Issues, 2017)
The main objective of this paper is to investigate the relation between the exchange rates and stock prices of the six GCC countries. The empirical results indicate that there is cointegration between stock prices and exchange rates in Kuwait, Bahrain and Oman. The Granger causality test reveals that exchange rates (in terms of the GBP) cause stock prices in all GCC countries, while stock prices cause exchange rates in Oman and Kuwait. Conversely, the empirical evidence indicates that exchange rates (in terms of the JPY) cause stock prices in Kuwait, while there is only one case of bidirectional causality between stock prices and exchange rates (the case of Oman). Keywords; Exchange rate, stock price, basket currency, peg currency, cointegration, and Granger causality. JEL Classifications: A10, A12, C13